Entrepreneurial Orientation Of Women Entrepreneur: A Bibliometric Analysis - Damayanti, Reza; Purnomo, Margo; Purbasari, Ratih (Archives of Business Research, 2023)
This paper wants to provide knowledge about the distribution of research on women entrepreneurs in the world, both at the country and organization levels. This research uses the VOSviewer 1.6.18 data processing application, namely co-authorship by countries and organizations. Women entrepreneurs encounter a number of hurdles while starting and running businesses, particularly in emerging and developing markets. Studies on women's motives for establishing a business, their capacity to acquire money, and varied success levels among men and women entrepreneurs demonstrate that the disparity between involvement and business performance appears to be similar across cultures and countries. Future research should look into women entrepreneurs at the organizational level, according to the recommendations.